THEORETICAL AND PRACTICAL BASIS OF CONTENT AND LANGUAGE INTEGRATED LEARNING - CLIL IN HIGHER EDUCATION - Nguyễn, Thanh Tâm (NHÀ XUẤT BẢN ĐẠI HỌC QUỐC GIA HÀ NỘI, 2019)
In recent years, there appear various novel trends in foreign language teaching/ learning in association with subject-matter courses. CLIL - content and language integrated learning is one of these trends; this method is becoming a growing trend in many countries, including Vietnam. However, in comparison to the history and development of this method in the world, it is quite new in Vietnam with a few years of development. As a new trend, this method is controversial and there are still people who are unclear about it. This study focuses on theoretical and practical bases which support the integration of content and language (especially English) in higher education. The study consists of three main parts: Theoretical basis, Practical basis of content and language (English) integrated learning and Suggest some practical solutions in order to effectively implement this method at higher education institutions in Vietnam.